PENGEMBANGAN MEDIA PEMBELAJARAN INTERAKTIF BERBANTUAN WORDWALL MATA PELAJARAN PENDIDIKAN PANCASILA MATERI KERAGAMAN BUDAYA INDONESIA KELAS V SD - Fatimah Azahro Damanik; Dinda Yarshal; Nila Lestari; Nurmairina (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This research is a research and development (R&D) that aims to (1) validate the development of interactive learning media assisted by WordWall for Pancasila education subjects on Indonesian cultural diversity. (2) the practicality of interactive learning media assisted by WordWall and (3) determine the improvement in student learning outcomes after using interactive learning media assisted by WordWall. This research procedure adapts the ADDIE Branch development model, namely development consisting of five stages including (analysis), design (design), development (development), implementation (implementation), and evaluation (evaluation). The results of this study are in the form of learning media assisted by WordWall which are validated by media experts and material experts, practical as seen from teacher responses and improvement in student learning outcomes as seen from answer scores. The average result of validation by material experts is 84% ​​with the criteria of